Special education libraries areas of greatest needs - Macasero, Joseph Persival B. 1980- (2007)
The areas of greatest needs of special education libraries were the foci of this descriptive study. The respondents came from Quezon City Schools with SPED programs. Three sets of questionnaires for school administrators, SPED teachers and library in-charge were administered. Thirty-four schools answered at least one questionnaire while 15 agreed to participate in the interviews and ocular inspections. Descriptive and inferential procedures were also utilized. Results showed that the 77 respondents perceived that the library needs within two years will decrease in the next 3 years. Funding emerged as the area that needed the most attention. The absence of a librarian contributed to the poor service and collection of the library. Much has to be done to improve the miserable state of SPED libraries.